2022
DOI: 10.3390/cells11213421
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Role of Non-Canonical Amyloid β Isoforms in Alzheimer’s Disease

Abstract: Recent advances have placed the pro-inflammatory activity of amyloid β (Aβ) on microglia cells as the focus of research on Alzheimer’s Disease (AD). Researchers are confronted with an astonishing spectrum of over 100 different Aβ variants with variable length and chemical modifications. With the exception of Aβ1-42 and Aβ1-40, the biological significance of most peptides for AD is as yet insufficiently understood. We therefore aim to provide a comprehensive overview of the contributions of these neglected Aβ v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 471 publications
0
5
0
Order By: Relevance
“…7 Microglia have the ability to detect the presence of Aβ in the brain. 8 When encountered with Aβ plaques in healthy cells, they become reactive, indicating they are responding to abnormal protein accumulation. 8 Microglia in which Aβ has a direct interaction expresses a range of Berkeley Pharma Tech Journal of Medicine | 17 structurally diverse molecules, including TREM2, CD33, CD35, etc.…”
Section: Glial Cell Interaction With Aβmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Microglia have the ability to detect the presence of Aβ in the brain. 8 When encountered with Aβ plaques in healthy cells, they become reactive, indicating they are responding to abnormal protein accumulation. 8 Microglia in which Aβ has a direct interaction expresses a range of Berkeley Pharma Tech Journal of Medicine | 17 structurally diverse molecules, including TREM2, CD33, CD35, etc.…”
Section: Glial Cell Interaction With Aβmentioning
confidence: 99%
“…8 Microglia in which Aβ has a direct interaction expresses a range of Berkeley Pharma Tech Journal of Medicine | 17 structurally diverse molecules, including TREM2, CD33, CD35, etc. 8 These receptors are responsible for recognition and response to Aβ. 8…”
Section: Glial Cell Interaction With Aβmentioning
confidence: 99%
“…Aβ40 is more abundant whereas Aβ42 presents much higher toxicity and a greater aggregation tendency [28]. Compared with Aβ42, aggregates containing Aβ43 (a longer Aβ C-terminal variant) are more likely to induce cerebral Aβ deposition [29]. Longer Aβ variants (Aβ42 and Aβ43) tend to be detected in Alzheimer's disease patients, whereas shorter forms (Aβ37, Aβ38 and Aβ40) are more likely to be found in subjects with intact cognition [30][31][32].…”
Section: The Preclinical Stage Of Alzheimer's Disease Is a Long Periodmentioning
confidence: 99%
“…Interestingly, some studies have also indicated that Aβ can potentially act as an antimicrobial peptide, suggesting a protective role for Aβ (Deepak et al, 2016, Pastore et al, 2020). Extensive work seeking to identify how Aβ becomes toxic in the brain has pointed to certain Aβ isoforms, small oligomer intermediates, and Aβ localization as key determinants in toxicity (Busch et al, 2022, Gallego et al, 2022, Rosenblum, 2002). Despite these discoveries, the role of Aβ in AD is still unclear, creating a need for well-characterized, robust models.…”
Section: Introductionmentioning
confidence: 99%